PEMBUATAN GAME TOWER DEFENSE “DEFKNIGHTS” PADA WEB - James Feriady Sulistiyo; Jeanny Pragantha; Darius Andana Haris (Jurnal Ilmu Komputer dan Sistem Informasi, 2022)
“DefKnights” is a three-dimensional game that can be accessed using internet browser with the address https://galeri.fti.untar.ac.id/gamedevuntar/defknights/. This game was developed with Unity Game Engine. The player will build towers to defeat enemies. Testing methods was done by Blackbox testing, Alpha testing, and Beta Testing by survey form given to 30 respondents. Testing results show that “DefKnights” is an interesting game with an easy-to-understand gameplay.